Analisis Pengangguran Milenial Lulusan Perguruan Tinggi di Jawa Barat Tahun 2022 Menggunakan Firth Logit - Farihah, Raisa; Utomo, Agung Priyo (Jurnal Ketenagakerjaan, 2024)
In August 2022, Indonesia has an open unemployment rate (TPT) of 5,86 percent with the highest province, West Java at 8,31 percent, which is still quite far from the target of the 2020?2024 National Medium-Term Development Plan (RPJMN) of 3,6?4,3 percent. This situation is exacerbated by the highly educated labour force (diplomas and bachelors) which is only absorbed by 11,81 percent, and the percentage of highly educated millennial unemployment covered by the age of 25?44 years is 46,1 percent. This study was conducted to analyze the general picture and variables that affect millennial unemployment of university graduates in West Java in 2022 using the firth logit method. The data used is raw data from the August 2022 National Labor Force Survey (Sakernas) in West Java. The results of this study are 3.61 percent who have the status of unemployed millennial college graduates, then there are variables of marital status, ownership of training certificates, and work experience have a significant effect on the unemployment status of millennial college graduates in West Java in 2022.